Analysis of WiFi Network Performance Using Wireshark Based on QoS Parameters: A Case Study of IndiHome Network - Deska Rohendi; Abdul Nizar; Aisyah Aryandani; Ari Rudiyan (Universitas Islam Al-Azhar Mataram, 2026)
The rapid development of internet network technology demands reliable service quality so that user activities can run optimally. This study aims to analyze the performance of the IndiHome WiFi network with a speed of 75 Mbps based on Quality of Service (QoS) parameters, which include delay, throughput, packet loss, and jitter. The method used is descriptive quantitative by directly collecting data through the network packet capture process using the Wireshark version 4.6.4 application. Data collection was carried out through three measurement sessions for each internet activity, namely browsing, streaming, and downloading, to generate network traffic. The results showed that the average delay values for browsing, streaming, and download activities were 18.85 ms, 23.87 ms, and 31.61 ms, respectively. The average throughput values obtained were 12.41 Mbps for browsing, 28.55 Mbps for streaming, and 61.84 Mbps for download. The average packet loss values were 0.10%, 0.35%, and 0.59%, while the average jitter values were 3.21 ms, 6.83 ms, and 9.88 ms for each activity. Based on the TIPHON standard, the delay, packet loss, and jitter parameters are categorized as Very Good, while the throughput for browsing and streaming activities is categorized as Medium due to the nature of the activities that do not require full bandwidth usage. Overall, the IndiHome WiFi network with a speed of 75 Mbps has Very Good service quality and is suitable for supporting various digital activities simultaneously.